2016
DOI: 10.1016/j.acvd.2016.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of percutaneous pulmonary valve implantation procedural steps on leaflets histology and mechanical behaviour: An in vitro study

Abstract: Valved stent implantation procedural steps induced histological lesions on Melody(®) valve leaflets. Conversely, bovine and porcine pericardial valved stents were not histologically altered by in vitro manipulations, although their mechanical properties were significantly modified. These data could explain some of the long-term complications observed with these substitutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
1
14
1
Order By: Relevance
“…A selective propensity of bovine jugular tissue (the precursor of the Melody valve leaflets) to histological lesions during procedural steps45 and to bacterial adherence46 was shown in in‐vitro studies, especially after procedural manipulation‐induced leaflet damage 46. These findings are in line with the observed higher propensity of valves with bovine jugular vein leaflets (Melody valve and Contegra graft) to IE than pulmonary homografts 18, 19, 47.…”
Section: Discussionsupporting
confidence: 62%
“…A selective propensity of bovine jugular tissue (the precursor of the Melody valve leaflets) to histological lesions during procedural steps45 and to bacterial adherence46 was shown in in‐vitro studies, especially after procedural manipulation‐induced leaflet damage 46. These findings are in line with the observed higher propensity of valves with bovine jugular vein leaflets (Melody valve and Contegra graft) to IE than pulmonary homografts 18, 19, 47.…”
Section: Discussionsupporting
confidence: 62%
“…ex vivo studies present a mixed picture with one study demonstrating a higher likelihood of bacterial adhesion to bovine jugular venous valve leaflet tissue when compared to bovine pericardial leaflet tissue whereas another study demonstrated no significant difference . The transcatheter implantation technique, involving crimping and balloon expansion, has been hypothesized to potentially alter topography of the valve, providing a favorable site for bacterial adhesion …”
Section: Discussionmentioning
confidence: 99%
“…18,19 The transcatheter implantation technique, involving crimping and balloon expansion, has been hypothesized to potentially alter topography of the valve, providing a favorable site for bacterial adhesion. 20,21 The clinical presentation of IE following TCPVR is variable. The Suppressive long-term oral antibiotics are of unclear benefit, there is a lack of compelling data to support or refute this strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors explaining this remarkable difference have been discussed. One of the main differences between transcatheter and surgical valve replacement is possible valvular damage before percutaneous implantation during crimping and during balloon expansion, whereas surgical prostheses are placed directly in the RVOT without any manipulation [43]. There is a higher incidence of reported endocarditis in patients after Melody valve implantation compared with SAPIEN.…”
Section: Late Complicationsmentioning
confidence: 99%
“…Long-term anticoagulation or antiplatelet therapy was suggested to reduce the incidence of initial thrombus formation in an area of endothelial damage which could be the location of infective vegetations after transient bacteremia [43]. …”
Section: Late Complicationsmentioning
confidence: 99%